Submandibular Gland Excision: Analysis of 43 Cases - Reşit Murat Açıkalın; İsa Özbay; Bayram Veyseller; Burak Dikmen; Gülşah Acar; Ahmet Alp; Mehmet Toptaş (Haseki Tıp Bülteni, 2014)
Aim: To retrospectively evaluate indications for surgery, histopathological results and surgery complications in patients who underwent submandibular gland excision. Methods: We retrospectively analyzed indications for surgery, age, sex, histopathological results, and surgery complications in 43 patients who underwent submandibular gland excision in our hospital between 2008 and 2012. Results: A total of 43 patients [30 male (69.7%), 13 female (30.2%)] were included in the study. The minimum postoperative follow-up period was 6 months. The mean age of the patients was 42.4 years, ranging from 11 to 86 years. 30 (69.7%) had painless swelling, 10 (23.2%) had painful swelling after eating, and three (6.9%) patients had infections frequently with pus spilling into the mouth. According to the histopathological results, 39 benign and four malign materials were excised and, sialadenitis was the most frequent benign pathology. As complications of the surgery; marginal mandibular nerve injury was seen in 4 patients (1 patient with persistent and three patients with transient nerve damage) and 2 patients had hematoma after surgery. Conclusion: The distribution of submandibular gland materials according to the histopathological types was similar to that in the literature. Although marginal facial nerve injury is the most common complication of submandibular gland excision, it was observed in our cases that only one patient experienced permanent nerve damage. Therefore, we assume that submandibular gland excision is a safe surgical procedure. (The Medical Bulletin of Haseki 2014; 52: 199-201)